Hubungan Tingkat Pengetahuan dengan Upaya Perilaku Pencegahan Penularan Covid-19 Pada Kader Posyandu Di Dusun Krajan Desa Glundengan Kecamatan wuluhan Kabupaten jember - Rida Darotin (NURSING UPDATE : Jurnal Ilmiah Ilmu Keperawatan P-ISSN : 2085-5931 e-ISSN : 2623-2871, 2022)
Background: Problems in the respiratory tract are caused by a new variant of the Coronavirus Severe Acute Respiratory Syndrome Disease or known as Covid-19. This virus spreads from human to human rapidly. then all related parties are increasingly urged to take action in carrying out early detection of infections and preventing the spread of Covid-19 from occurring in order to reduce the number of Covid-19 cases. Purpose: This study aims to determine the relationship between the level of knowledge and behavioral efforts to prevent the transmission of Covid-19 in Posyandu Cadres. Methods: This type of research is descriptive with a cross sectional approach. The sample of this research is 50 Posyandu Cadres in Krajan Glundengan District Wuluhan-Jember. Results: The majority of respondents' knowledge levels are in the good category, the majority of posyandu cadres' behavior in efforts to prevent Covid-19 is in the positive category. The results of Fisher's test analysis with a P Value of 0.040 means that there is a relationship between the level of knowledge and efforts to prevent Covid-19 behavior in Posyandu Cadres. Conclusion: The better the level of knowledge of posyandu cadres about Covid-19, the more positive the efforts to prevent Covid-19 behavior.